Todos podem aprender : construindo caminhos conectados com a formação do educador que possibilitem o fazer pedagógico inclusivo - Nunes, Nora Helena Soares (2011)
The school inclusion is a complex process inserted in the organization of national education, what for requires transforming actions, so that the right of everyone to education be a collective movement, where access to the pleasure of learning is universal. The resistance of the traditional school to an inclusive process reflects its inability to act before the complexity of human relationships in the educational system. The inclusive school process takes into consideration the learning ability of all children, so the importance of the sensibility of the teacher to identify the characteristics of individual students and thus enhance their skills. However, it is also necessary the practical knowledge of relevant legislation, the state's participation through public policies and ongoing training of educators.